EKSPERIMENTASI MODEL PEMBELAJARAN NUMBERED HEADS TOGETHER (NHT) DENGAN METODE PENEMUAN TERBIMBING PADA MATERI KUBUS DAN BALOK DITINJAU DARI KEMAMPUAN SPASIAL DAN GAYA KOGNITIF SISWA - Hidayat, Abdul Aziz; Riyadi, Riyadi; Subanti, Sri (Jurnal Pembelajaran Matematika, 2015)
Abstract: The objective of this research was to investigate the difference of learning achievement in Mathematics on the learning of Cubes and Cuboids in each learning model viewed from the spatial abilities and the cognitive styles. This research used the quasi experimental research with the factorial design of 3x3x2. The proposed hypotheses of the research were analyzed by using the three-way analysis of variance with unbalanced cells. The results of the research are as follows. 1) The students instructed with the NHT learning model with guided discovery method have a better learning achievement in Mathematics than those instructed with the NHT learning model and those with the direct learning model, and the students instructed with the NHT learning model have a better learning achievement in Mathematics than those with the direct learning model. 2) The students with the high, moderate, and low spatial abilities have the same good learning achievement in Mathematics. 3) The students with the cognitive style of field independent have a better learning achievement in Mathematics than those with the cognitive style of field dependent. 4). In each category of the spatial abilities, the students instructed with the NHT learning model with guided discovery method have a better learning achievement in Mathematics than those instructed with the NHT learning model and those with the direct learning model, and the students instructed with the NHT learning model have a better learning achievement in Mathematics than those with the direct learning model. 5) In each category of the spatial abilities, the students instructed with the NHT learning model with guided discovery method have a better learning achievement in Mathematics than those instructed with the NHT learning model and those with the direct learning model, and the students instructed with the NHT learning model have a better learning achievement in Mathematics than those with the direct learning model.Keywords: NHT, guided discovery, spatial abilities, Â and cognitive styles.